2022
DOI: 10.1111/vsu.13759
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive video‐assisted parathyroidectomy in dogs: Technique description and feasibility study

Abstract: Objective To describe a minimally invasive approach to the parathyroid gland for the treatment of primary hyperparathyroidism. Study design Surgical technique description and clinical case report. Animals Five canine cadavers and 5 client‐owned dogs with primary hyperparathyroidism. Methods A surgical technique for minimally invasive video‐assisted parathyroidectomy (MIVAP), described for humans, was adapted for dogs. With the dog in dorsal recumbency, a 15 mm incision was made on the midline, 1 finger width c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…One recent study in canine cadavers and clinical cases adapted and described the technique for minimally invasive video‐assisted parathyroidectomy 22 . While it demonstrated that the technique was feasible in dogs, information such as signalment, histological diagnosis, and clinical outcomes were unlikely representative of the general population due to the small number of cases 22 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One recent study in canine cadavers and clinical cases adapted and described the technique for minimally invasive video‐assisted parathyroidectomy 22 . While it demonstrated that the technique was feasible in dogs, information such as signalment, histological diagnosis, and clinical outcomes were unlikely representative of the general population due to the small number of cases 22 .…”
Section: Discussionmentioning
confidence: 99%
“…One recent study in canine cadavers and clinical cases adapted and described the technique for minimally invasive video‐assisted parathyroidectomy 22 . While it demonstrated that the technique was feasible in dogs, information such as signalment, histological diagnosis, and clinical outcomes were unlikely representative of the general population due to the small number of cases 22 . Minimally invasive video‐assisted parathyroidectomy has a steep learning curve (utilization of potential space and not the natural body cavity, stabilization of the scope in the absence of cannulas) and requires specialized equipment that are designed specifically for the procedure 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations